The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsomega.9b01656
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Doping of Europium in Gadolinium Borate Microparticles at Mesoscale Toward Efficient Production of Red Phosphors

Abstract: The ideal product of rare-earth-doped phosphors should have uniform particle size distribution and homogeneous doping ions in each particle, and therefore, intensified micromixing at mesoscale is highly required. In this article, inspired by the concept of “mesoscience”, we demonstrate the tuning of Eu3+ doping in GdBO3 microparticles at mesoscale by a high-gravity-assisted reactive precipitation-coupled calcination process. The high-gravity environment and tiny droplets generated by the high-gravity rotating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Today, semiconductor lighting is receiving increasing attention because of its environment-friendly nature and high energy efficiency. At present, the light-emitting diode (LED)-related industries are considered as an important way to promote energy conservation and emission reduction and mitigate global climate change. White LEDs have many outstanding advantages including their energy-saving and environment-friendly nature and long service life, so they have undoubtedly become new-generation solid-state lighting sources. The foremost prevalent strategy to manufacture white LEDs is based on InGaN blue LED chips with YAG:Ce 3+ yellow-emitting phosphors. Although this fabrication method shows high luminescence efficiency, the lack of red component in the white spectrum does not meet the requirement of warm-white light emission for general lighting. In order to obtain high-color rendering index (CRI) warm-white light, an alternative method is to excite red-, green-, and blue-emitting (RGB tricolor) phosphors using near-ultraviolet (near-UV) LED chips. In this method, the red phosphor is an indispensable component in white LED fabrication. However, the commercial nitride- and sulfide-based red phosphors have the disadvantages of strict synthesis conditions and poor chemical stability, which have great negative effects on their large-scale production and application. In sharp contrast, the oxide-based phosphors have good chemical stability, simple synthesis methods, and high luminescence efficiency. Therefore, the search for an efficient red-emitting oxide phosphor as a color converter for near-UV-excitable white LEDs is a meaningful study.…”
Section: Introductionmentioning
confidence: 99%
“…Today, semiconductor lighting is receiving increasing attention because of its environment-friendly nature and high energy efficiency. At present, the light-emitting diode (LED)-related industries are considered as an important way to promote energy conservation and emission reduction and mitigate global climate change. White LEDs have many outstanding advantages including their energy-saving and environment-friendly nature and long service life, so they have undoubtedly become new-generation solid-state lighting sources. The foremost prevalent strategy to manufacture white LEDs is based on InGaN blue LED chips with YAG:Ce 3+ yellow-emitting phosphors. Although this fabrication method shows high luminescence efficiency, the lack of red component in the white spectrum does not meet the requirement of warm-white light emission for general lighting. In order to obtain high-color rendering index (CRI) warm-white light, an alternative method is to excite red-, green-, and blue-emitting (RGB tricolor) phosphors using near-ultraviolet (near-UV) LED chips. In this method, the red phosphor is an indispensable component in white LED fabrication. However, the commercial nitride- and sulfide-based red phosphors have the disadvantages of strict synthesis conditions and poor chemical stability, which have great negative effects on their large-scale production and application. In sharp contrast, the oxide-based phosphors have good chemical stability, simple synthesis methods, and high luminescence efficiency. Therefore, the search for an efficient red-emitting oxide phosphor as a color converter for near-UV-excitable white LEDs is a meaningful study.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, trivalent rare earth cations with ionic radii similar to that of Ca 2+ can be successfully incorporated into the crystal lattice . It is desired for the high-performance rare earth doped phosphors to achieve homogeneous doping of ions in the host matrixes and a uniform particle size distribution (PSD) …”
Section: Introductionmentioning
confidence: 99%
“…23 It is desired for the high-performance rare earth doped phosphors to achieve homogeneous doping of ions in the host matrixes and a uniform particle size distribution (PSD). 24 As is known, the uniform spatial concentration distribution and higher supersaturation degree in the reactive precipitation process are beneficial to homogeneous nucleation and smaller particle size. 25−27 It has been confirmed that a micromixing time (t M ) less than the nucleation induction time (t N , on the order of 1 ms for the reactive precipitation in aqueous solution) is crucial to achieving the above conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several aspects affecting particle size distribution such as molecule-scale and nanoscale micromixing processes are challenging when scaling up these processes . The high gravity technology based on the use of a rotating packed-bed (RPB) reactor is an efficient tool for process intensification to meet the requirements of homogeneous micromixing and generating uniform nanoparticles. , …”
Section: Introductionmentioning
confidence: 99%